Spontaneous Pulmonary Hypertension Associated With Systemic Sclerosis in P‐Selectin Glycoprotein Ligand 1–Deficient Mice. Issue 3 (28th January 2020) - González‐Tajuelo, Rafael; de la Fuente‐Fernández, María; Morales‐Cano, Daniel; Muñoz‐Callejas, Antonio; González‐Sánchez, Elena; Silván, Javier; Serrador, Juan Manuel; Cadenas, Susana; Barreira, Bianca; Espartero‐Santos, Marina; Gamallo, Carlos; Vicente‐Rabaneda, Esther F.; et al.
Abstract : Objective: Pulmonary arterial hypertension (PAH), one of the major complications of systemic sclerosis (SSc), is a rare disease with unknown etiopathogenesis and noncurative treatments. As mice deficient in P‐selectin glycoprotein ligand 1 (PSGL‐1) develop a spontaneous SSc‐like syndrome, we undertook this study to analyze whether they develop PAH and to examine the molecular mechanisms involved. Methods: Doppler echocardiography was used to estimate pulmonary pressure, immunohistochemistry was used to assess vascular remodeling, and myography of dissected pulmonary artery rings was used to analyze vascular reactivity. Angiotensin II (Ang II) levels were quantified by enzyme‐linked immunosorbent assay, and Western blotting was used to measure Ang II type 1 receptor (AT1 R), AT2 R, endothelial cell nitric oxide synthase (eNOS), and phosphorylated eNOS expression in lung lysates. Flow cytometry allowed us to determine cytokine production by immune cells and NO production by endothelial cells. In all cases, there were 4–8 mice per experimental group. Results: PSGL‐1 −/− mice showed lung vessel wall remodeling and a reduced mean ± SD expression of pulmonary AT2 R (expression ratio [relative to β‐actin] in female mice age >18 months: wild‐type mice 0.799 ± 0.508 versus knockout mice 0.346 ± 0.229). With aging, female PSGL‐1 −/− mice had impaired up‐regulation of estrogen receptor α (ERα) and developed lung vascular endothelial dysfunction coinciding with an increase in mean ± SEM pulmonary Ang II levels (wild‐type 48.70 ± 5.13 pg/gm lung tissue versus knockout 78.02 ± 28.09 pg/gm lung tissue) and a decrease in eNOS phosphorylation, leading to reduced endothelial NO production. These events led to a reduction in the pulmonary artery acceleration time:ejection time ratio in 33% of aged female PSGL‐1 −/− mice, indicating pulmonary hypertension. Importantly, we found expanded populations of interferon‐γ–producing PSGL‐1 −/− T cells and B cells and a reduced presence of regulatory T cells. Conclusion: The absence of PSGL‐1 induces a reduction in Treg cells, NO production, and ERα expression and causes an increase in Ang II in the lungs of female mice, favoring the development of PAH.